Simple cultural test for relative cellulolytic activity of fungi - R.S. MATHUR2, SAROJINI KANOTRA (VARMA)1 and (Indian Phytopathology, 2002)
A study was conducted to determine a simple and rapid procedure to examine cellulolytic activity of secondary invading organisms and to determine the appropriate carbon concn for max. cellulase production. Fungal cultures examined were Trichoderma reesei [T. longibrachiatum], Aspergillus wentii, Pleurotus sajor-caju, Pleurotus florida, Trichoderma viride, Coprinus cinereus, C. comatus, Chaetomium globosum, A. fumigatus, A. awamori and Trichurus spiralis. Highest cellulase activity was recorded in T. reesei on a cellulose media and P. sajor-caju on CMC and lactose media.